Potensi Produksi dan Kinerja Investasi Industri Pengolahan Kelapa Terpadu di Provinsi Aceh - Romano Romano (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
ABSTRACT. The Province of Aceh has the large potential of palm plant development with high production value, when supported by an integrated coconut industry. Today with potential expansion of coconut in 8 point production centers has 210.400 ha, we needs the processing technology that can utilize a by product and product primer, such as coir and coconut shell. Research has been conducted in four districts of Aceh by using census method. The results showed the coefficient of technology produced from 12 unit integrated coconut processing industry is 0.6806. With an investment of between Rp 342 million to Rp 825 million to produce a value of Rp 1,543,707,300 to Rp 3,721,320,000 in industrial economic life of 10 years. Efficiency of integrated technology is still relatively low oil caused a number of factors and allocation of equipment investment. There are still residual value (salvage value) is still a waste in the benefits component of coconut that has not been exploited by employers.